Advertisement Remove all ads

Given X = `(Sqrt(A^2 + B^2) + Sqrt(A^2 - B^2))/(Sqrt(A^2 + B^2) + Sqrt(A^2 - B^2))` Use Componendo and Dividendo to Prove that B^2 = (2a^2x)/(X^2 + 1) - Mathematics

Given x = `(sqrt(a^2 + b^2) + sqrt(a^2 - b^2))/(sqrt(a^2 + b^2) + sqrt(a^2 - b^2))`

Use componendo and dividendo to prove that b^2 = (2a^2x)/(x^2 + 1)

Advertisement Remove all ads

Solution

x = `(sqrt(a^2 + b^2) + sqrt(a^2 - b^2))/(sqrt(a^2 + b^2) + sqrt(a^2 - b^2))`

by componendo and dividendo

`(x + 1)/(x - 1) = (sqrt(a^2 + b^2) + sqrt(a^2 - b^2) + sqrt(a^2 + b^2) - sqrt(a^2 - b^2))/(sqrt(a^2 + b^2) + sqrt(a^2 - b^2) - sqrt(a^2 + b^2) + sqrt(a^2 - b^2))`

`(x + 1)/(x - 1) = (2sqrt(a^2 + b^2))/(2sqrt(a^2 - b^2))`

Squaring both sides

`(x^2 + 2x + 1)/(x^2 - 2x + 1) = (a^2 + b^2)/(a^2 - b^2)`

By componendo and dividendo

`((x^2 + 2x + 1) + (x^2 - 2x + 1))/((x^2 + 2x + 1) - (x^2 - 2x + 1)) = ((a^2 + b^2) + (a^2 - b^2))/((a^2 + b^2) - (a^2 - b^2))`

`=> (2(x^2 + 1))/(4x) = (2a^2)/(2b^2)`

`=> (x^2 + 1)/(2x) = a^2/b^2`

`=> b^2 = (2a^2 x)/(x^2 + 1)`

Concept: Componendo and Dividendo Properties
  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

Selina Concise Maths Class 10 ICSE
Chapter 7 Ratio and Proportion (Including Properties and Uses)
Exercise 7 (D) | Q 19 | Page 102
Advertisement Remove all ads

Video TutorialsVIEW ALL [1]

Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×